Robust nonfullerene solar cells approaching unity external quantum efficiency enabled by suppression of geminate recombination - Tan, Ching Hong; Gasparini, Nicola; McCulloch, Iain; Durrant, James R.; Brabec, Christoph J.; Hamid, Zeinab; Song, Xin; Wadsworth, Andrew; Baran, Derya; Wehbe, Nimer; Kirchartz, Thomas; Neophytou, Marios; et al. (My University, 2018)
Nonfullerene solar cells have increased their efficiencies up to 13%, yet quantum efficiencies are still limited to 80%. Here we report efficient nonfullerene solar cells with quantum efficiencies approaching unity. This is achieved with overlapping absorption bands of donor and acceptor that increases the photon absorption strength in the range from about 570 to 700 nm, thus, almost all incident photons are absorbed in the active layer. The charges generated are found to dissociate with negligible geminate recombination losses resulting in a short-circuit current density of 20 mA cm -2 along with open-circuit voltages >1 V, which is remarkable for a 1.6 eV bandgap system. Most importantly, the unique nano-morphology of the donor:acceptor blend results in a substantially improved stability under illumination. Understanding the efficient charge separation in nonfullerene acceptors can pave the way to robust and recombination-free organic solar cells.
Keywords: Organic photovoltaics; Solar cells; Fullerenes